2002
DOI: 10.1021/jf011210d
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antioxidant Properties of Free and Bound Phenolic Acids from Native and Malted Finger Millet (Ragi, Eleusine coracana Indaf-15)

Abstract: Free and bound phenolic acids were isolated from native and malted finger millet (ragi, Eleusine coracana Indaf-15), and their antioxidant properties were evaluated. Protocatechuic, gallic, and caffeic acids were found to be the major free phenolic acids. A 3-fold decrease was observed in protocatechuic acid content, whereas the decrease was marginal in the case of caffeic acid upon 96 h of malting. However, the contents of other free phenolic acids such as gallic, vanillic, coumaric, and ferulic acids increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(62 citation statements)
references
References 22 publications
7
55
0
Order By: Relevance
“…For example, Oki et al [34] observed that radical-scavenging ability in red-hulled and black-hulled rice depended on the concentrations of proanthocyanidins and anthocyanins, respectively. During the process of finger millet malting, the contents of phenolic acids were changed, reflecting their antioxidant capacity [35]. The high levels of flavonols, quercetin and kaempferol contents were associated with enhanced stress tolerance capacity of white clover under UV-B radiation and drought conditions [31].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Oki et al [34] observed that radical-scavenging ability in red-hulled and black-hulled rice depended on the concentrations of proanthocyanidins and anthocyanins, respectively. During the process of finger millet malting, the contents of phenolic acids were changed, reflecting their antioxidant capacity [35]. The high levels of flavonols, quercetin and kaempferol contents were associated with enhanced stress tolerance capacity of white clover under UV-B radiation and drought conditions [31].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Generally, it is believed that consumption of plant phenolics decreases the risk of diseases related to oxidative stress. 5 Wine, as a complex matrix containing several hundreds of different chemical compounds, 6,7 presents an analytical challenge, especially for identification and quantification of compounds in low concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…In the study, 50 µg/mL of the seed coat extract showed higher (86 %) antioxidant activity when compared to whole flour (27%) at the same concentration. Subba Rao and Muralikrishna, 44 also investigated the antioxidant activity of free and bound phenolic acids in native and malted finger millet extracts. Results of the study showed that free phenolic acids in the malted extract exhibited higher antioxidant activity coefficient (770.00 ± 7.8) compared to the bound phenolic acids (570.0 ± 6.0).…”
Section: Antioxidant Activitymentioning
confidence: 99%